Single-cell mass cytometric analysis of peripheral immunity and multiplex plasma marker profiling of non-small cell lung cancer patients receiving PD-1 targeting immune checkpoint inhibitors in comparison with platinum-based chemotherapy - Neuperger, Patrícia; Szalontai, Klára; Gémes, Nikolett; Balog, József Á.; Tiszlavicz, László; Furák, József; Lázár, György; Puskás, László G.; Szebeni, Gábor J. (Frontiers in Immunology, 2023)
The effect of platinum-based chemotherapy (Chem.) and second or multiple-line immune checkpoint PD-1 blocking therapy by Nivolumab or Pembrolizumab (ICI) was assayed in the peripheral blood of non-small cell lung cancer (NSCLC) patients. Flow cytometry was used to detect NSCLC-related antigen binding IgG antibodies. The Luminex MagPix multiplex bead-based cytokine/chemokine detecting system was used to quantitatively measure 17 soluble markers in the plasma samples. Single-cell mass cytometry was applied for the immunophenotyping of peripheral leukocytes. The incubation of patient-derived plasma with human NSCLC tumor cell lines, such as A549, H1975, and H1650 detected NSCLC specific antibodies reaching maximum up to 32% of reactive IgG positive NSCLC cells. The following markers were detected in significantly higher concentration of the plasma of Chem. group versus healthy non-smoker and smoker controls:BTLA, CD27, CD28, CD40, CD80, CD86, GITRL, ICOS, LAG-3, PD-1, PD-L1, TLR-2.The following markers were detected in significantly higher concentration of the plasma of ICI group versus healthy non-smoker and smoker controls:CD27, CD28, CD40, GITRL, LAG-3, PD-1, PD-L1, TLR-2.We showed the induction of CD69 and IL-2R on CD4+CD25+ T-cells upon chemotherapy, the exhaustion of one CD8+ T-cell population was detected by the loss of CD127 and decrease of CD27. CD19+CD20+, CD79B+, or activated B-cell subtypes showed CD69 increase and downregulation of BTLA, CD27, and IL-2R in NSCLC patients following chemotherapy or ICI. Peripheral immunophenotype caused by chemotherapy or PD-1 blocking was shown in the context of advanced NSCLC.